UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK ALOUD PAIR PROBLEM SOLVING (TAPPS) DI SEKOLAH DASAR - Khotimah, Husna; Fitra Surya, Yenni; Aprinawati, Iis; Hana Pebriana, Putri; Ananda, Rizki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the low results of mathematics problem-solving skills of students in grade IV MI AL FALAH. One of the solutions to overcome this problem is to use the Think Aloud Pair Problem Solving (TAPPS) learning model. The purpose of this research is to improve problem-solving skills in mathematics learning material about integers. This research method is a class action research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time will be held in August 2025. The subjects of this study are 20 grade IV students, consisting of 13 male students and 7 female students. Data collection techniques are in the form of observation, tests and documentation. The results of this study can be concluded that the results of students' mathematical problem-solving skills in the material of numerals in class IV MI AL FALAH preaction have an average score of 49.75 with classical completeness of 25%, then in the first cycle meeting 1 has increased to 57.40 with classical completeness of 40%, and in the first cycle of meeting 2 it has increased to 64.33 with classical completeness of 50%. Furthermore, in the second cycle of meeting 1, an average score of 79.02 was obtained with classical completeness of 90%, and in the second cycle of meeting 2, an average score of 83.84 was obtained with classical completeness of 100%. Thus, it can be concluded that students' mathematical problem-solving skills can be improved by applying the Think Aloud Pair Problem Solving (TAPPS) model.